(3CSGSjGJ EOGQI GdCYeGd (B:s (3egGQGJ fXQjI h JWHjbjI (B/s - (3MQjR, SGej eMeO gTGes ((3YeGf(B: s (3OGQ bfOjd ddfTQ hGdJhRjY(B, s, 2008)
(3eaghe GdegGQI hGdEHOGY(B- (3GdEOGQI hGdJZjjQ GdJfXjej(B- (3egGQGJ hafhf aj YGde GdEOGQI(B- (3GdEHOGY hGdfLGM aj YGde GdEOGQI(B- (3GdNHQI hGdSjGSI aj YGde GdEOGQI(B- (3GdYjhH aj EOGQI GdCYeGds
(3GdeQGLY U(B.297s
Keywords: (3EOGQI GdCYeGds; (3GdEHOGYs; (3GdEOGQI GdYGeIs